Undifferentiated colonic neoplasm with SMARCA4 germline gene mutation and loss of SMARCA4 protein expression: a case report and literature review - Huanli Duan; Wei Gao; Leiming Wang; Feng Cao; Lianghong Teng (BMC, 2021)
Abstract Background Nonsense mutation or inactivation of SMARCA4 (BRG1) is associated with a monomorphic undifferentiated histological appearance in tumors at different sites. The association between SMARCA4 alteration and undifferentiated colonic carcinoma needs to be further elucidated. Methods A 61-year-old male patient presented to the hospital with intermittent epigastric pain in the right upper abdomen and abdominal distension. The enhanced computed tomography detected a mass in the hepatic flexure of the colon and multiple liver metastases. Results The right hemicolectomy contained a 4.5-cm undifferentiated malignancy with cells arranged in sheets, abundant necrosis, and areas showing rhabdoid morphology. The immunohistochemistry result showed that these tumor cells were focally positive for cytokeratin (CK), CK8, and CK18; however, diffusely positive for vimentin, P53, Fli-1, and SALL-4. Notably, tumor cells showed a heterogeneous loss of SMARCA4 expression pattern and intact SMARCB1 expression. Next-generation sequencing showed a germline SMARCA4 c.3277C>T(p.R1093*)mutation, somatic APC mutation, and no abnormal SMARCB1 gene. The tumor exhibited microsatellite stability, negative PD-L1 expression, and few infiltrating CD8 + T cells. The patient died a month later after surgery. Conclusions We presented a rare case of undifferentiated colonic neoplasm with loss of SMARCA4 protein expression and germline SMARCA4 mutation. Moreover, the role of SMARCA4 alterations in tumor diagnosis and treatment was also summarized.